Dinamika Politik dalam Pembentukan Hukum Keluarga Islam: Analisis Sosiologi Hukum Islam - Wartono, Nanang; Sayuti, Hendri (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to analyze the political dynamics in the formation of Islamic family law in Indonesia through the perspective of the sociology of Islamic law. The study focuses on how the interaction between the state, religious scholars, and society shapes the character of family law, adapting it to social change and the values of modernity. This study uses a qualitative approach with a descriptive-analytical library research method. Data were obtained from various scientific literature, laws and regulations, and official documents related to Islamic family law. The analysis was conducted using content analysis and thematic analysis techniques to identify ideological patterns, power relations, and political influences in the formation of Islamic law. The results show that Islamic family law in Indonesia is the result of political negotiations between conservative and reformist groups, in which the state acts as a mediator between religious authority and the demands of modernity. The role of religious scholars and religious organizations is ambivalent, serving as both guardians of morality and tools of political legitimacy. Furthermore, women's involvement remains symbolic, and the legislative process is often influenced by electoral interests and the politicization of religious identity. This study confirms that Islamic family law is not merely a normative product but also an arena of complex social and political interactions. The implication is that the renewal of Islamic family law must be directed towards a participatory, inclusive, and socially just paradigm to align with the principles of maqāṣid al-shari‘ah and the needs of modern society.